Consumer's perceptions of brand origin in relation to apparel quality - Santiago, Dianna Marisse U.; Caragay, Kristyn T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The study examined the influence of Filipino consumers' perception of an apparel brand's origin and its relation to the quality (workmanship, comfort, value for money, fit and style) of its products. The study also confirmed if the correlation of brand origin and quality can explain the growth of international brands and downward sales of local brands in the Philippines. The study created six(6) mock-up brands suggesting three (3) brand origins which were Italy, China and the Philippines. A survey was conducted among 100 Filipino respondents. It was found that there is a relationship between the respondents' perceptions of apparel quality and its perceived brand origin. they perceived the brand that suggested an Italian brand origin the highest in quality apparel followed by the brand with a Chinese brand origin. There were four (4) mock-up brands in the study that hinted a Filipino brand origin, and three of those brands were perceived by the respondents as the lowest in quality apparel among the six. The study concludes that country stereotypes still exist and affects consumers' perceptions of quality. Therefore the influx and success of foreign brands, may be attributed to the respondents' perception of those foreign brands. Since the study found out that a factor in determining the brand origin and quality relies on visual aspects of the marketing collateral, the researcher recommends to improve the advertisements of the Filipino brands to successfully compete with foreign brands.
Thesis (BSCT)--University of the Philippines Diliman.
Keywords: Consumers' preferences -- Philippines; Brand choice